2019
DOI: 10.3390/f10100853
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Biases in Global Tree Cover Products: A Case Study in Costa Rica

Abstract: Global tree cover products are widely used in analyses of deforestation, fragmentation, and connectivity, but are rarely critically assessed. Inaccuracies in these products could have consequences for future decision making, especially in data-poor regions like the tropics. In this study, potential biases in global and regional tree cover products were assessed across a diverse tropical country, Costa Rica. Two global tree cover products and one regional national forest cover map were evaluated along biophysic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 58 publications
0
34
1
Order By: Relevance
“…In the case of study 2, their methodological error was using the Hansen et al (2013) data to estimate existing tree cover in drylands. Bastin, Berrahmouni, et al (2017) Cunningham, Cunningham, and Fagan (2019) found that the HGFC product begins to dramatically underestimate tree cover below approximately 2,270 mm of mean annual precipitation (e.g., tropical dry forest). In this study, I show that the HGFC product underestimates tree cover even at very low cover in hyperarid systems (Figure 3), and that this bias in drylands has a large cumulative effect on global canopy cover estimates.…”
Section: Aus E S Of Mis -E S Timate Smentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of study 2, their methodological error was using the Hansen et al (2013) data to estimate existing tree cover in drylands. Bastin, Berrahmouni, et al (2017) Cunningham, Cunningham, and Fagan (2019) found that the HGFC product begins to dramatically underestimate tree cover below approximately 2,270 mm of mean annual precipitation (e.g., tropical dry forest). In this study, I show that the HGFC product underestimates tree cover even at very low cover in hyperarid systems (Figure 3), and that this bias in drylands has a large cumulative effect on global canopy cover estimates.…”
Section: Aus E S Of Mis -E S Timate Smentioning
confidence: 99%
“…(2019) found that the MODIS VCF product underestimated tree cover by 5.6% in shrublands and savannas, very close to the 5.9% bias observed in this study for the HGFC product. This particular challenge likely arises from multiple causes (Cunningham et al., 2019; Sexton et al., 2015; Smith et al., 2019). First, it may be caused by intra‐ and inter‐annual variability in tree and herbaceous phenology in response to rainfall, which can lead to variable estimates of cover over time (Smith et al., 2019).…”
Section: Causes Of Mis‐estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…This low accuracy of the ADP method may be partially attributed to the reliance on optical images. Previous studies have shown that the use of optical images makes it difficult to differentiate between forest and dense canopy crops such as mature oil palm [17,39] as well as perennial agricultural crops and plantations of less than 5 m height such as pineapple, tea, and soybean as tree cover [3,40] due to similar spectral signal.…”
Section: Discussionmentioning
confidence: 99%
“…Disagreement between MapBiomas and TerraClass has been shown for classes other than forest (Körting et al 2020) whereas others have criticized the products for not following good practice guidelines in accuracy assessment (Zalles et al 2019). Others such as Cunningham et al (2019) critically assess the utility of the GFC dataset with recommendations to use with caution in area that do not meet criteria including high aseasonal rainfall, low relief, and low cropland area. Likewise, Galiatsatos et al (2020) found that the GFC dataset should not be used for precise estimates of forest cover change in countries with large areas of forest cover and low levels of deforestation.…”
Section: Discussionmentioning
confidence: 99%